Sixth International Congress on Industrial Applied Mathematics, ICIAM07, Zürich 2007 and GAMM Annual Meeting, Zürich 2007 (Proceedings in applied mathematics and mechanics, 2007)
Volume 7 (2007) of PAMM “Proceedings in Applied Mathematics and Mechanics” assembles the Minisymposia and Contributed papers to both the 6th International Congress on Industrial and Applied Mathematics, ICIAM07, held 16–20 July 2007 in Zürich and the 78th Annual Meeting of the Gesellschaft für Angewandte Mathematik und Mechanik, held as an embedded meeting of ICIAM07. The contributions are grouped according to the minisymposia of ICIAM07 and GAMM annual meeting respectively and the subject areas of ICIAM07 and the sections of the GAMM annual meeting. 1 ICIAM07 Minisyposia 01–17 ICIAM07 Minisymposia: 01 Computing 1‐01‐01 Applied analysis meets scientific computing 1‐01‐02 Microlocal analysis meets scientific computing 1‐01‐03 High‐dimensional analysis meets scientific computing 1‐01‐04 Parallel MATLAB 1‐01‐05 Math on the web: content development and implementation 1‐01‐06 High‐level software for the numerical solution of partial differential equations 1‐01‐07 Recent advances in software tools for scientific computing 1‐01‐08 Combinatorial scientific computing 1‐01‐09 Writing scientific software: experience with using, developing and teaching 1‐01‐10 Image processing: computation and applications 1‐01‐11 Laplacian eigenfunctions and their applications 1‐01‐12 The role of scale and orientation in mathematical image analysis 1‐01‐13 Novel matrix methods for internet‐data mining 1‐01‐14 The AIM@SHAPE digital shape workbench as an e‐Science collaboration tool 1‐01‐15 Level‐set methods: current development ICIAM07 Minisymposia: 02 Numerical Analysis 1‐02‐01 Verified computations with applications 1‐02‐02 Multiscale methods for strongly‐heterogeneousmedia 1‐02‐03 Multiscale porous media: solvers 1‐02‐04 Nonlinear eigenvalue problems 1‐02‐05 Computational methods for structured eigenvalue problems 1‐02‐06 Matrix functions: methods and applications 1‐02‐07 Solution methods for sequences of linear systems and applications 1‐02‐08 Iterative solution of saddle‐point systems arising in PDE‐constrained optimization 1‐02‐09 Developments in algebraic multigrid methods for real‐world applications 1‐02‐10 Large‐scale eigenvalue problems 1‐02‐11 Mathematical topics in matrix iterations 1‐02‐12 Structured matrix algorithms: new methods 1‐02‐13 Structured matrix algorithms: complexity and stability 1‐02‐14 Model reduction: theory, methodology and software 1‐02‐15 Model reduction: structured and higher‐order systems 1‐02‐16 Model reduction in circuit simulation 1‐02‐17 Numerical linear algebra in image processing 1‐02‐18 Tensor decompositions and their application 1‐02‐19 Numerical multilinear algebra: a new beginning 1‐02‐20 Preconditioning of symmetric indefinite systems in large‐scale applications 1‐02‐21 Preconditioners for sequences of linear systems 1‐02‐22 Approximate algebraic methods for computer‐aided geometric design 1‐02‐23 Sparse grids for high‐dimensional approximation 1‐02‐24 Algorithms for high‐dimensional problems 1‐02‐25 Multivariate numerical integration 1‐02‐26 Modern constructions of low‐discrepancy sequences 1‐02‐27 Robust integral equation methods for high‐frequency problems 1‐02‐28 Spectral computations for integral operators 1‐02‐29 Taylor‐model methods and interval methods: techniques 1‐02‐30 Taylor‐model methods and interval methods: applications 1‐02‐31 The numerical solution of differential equations: recent advances 1‐02‐32 Artificial boundary conditions for linear and nonlinear Schrdinger equations 1‐02‐33 Modeling and numerical methods for multi‐dimensional and multi‐physical problems 1‐02‐34 Applications and numerical approximations of geometric partial differential equations 1‐02‐35 Recent advances in front propagation modelling and applications 1‐02‐36 Time integration of evolution equations 1‐02‐37 Solution of the master equation in biochemistry 1‐02‐38 High‐resolution discretizations of initial boundary‐value problems 1‐02‐39 Mathematical analysis and numerical simulation for Bose–Einstein condensation 1‐02‐40 Numerical methods for option pricing 1‐02‐41 High‐order shock capturing methods for non‐linear hyperbolic partial differential equations 1‐02‐42 Numerical methods for multicomponent flows 1‐02‐43 High‐order methods for wave propagation and flow problems in complex geometries 1‐02‐44 New directions in PDE simulations 1‐02‐45 Recent advances in interface methods and applications in multi‐phase problems 1‐02‐46 Multiscale porous media: discretizations 1‐02‐47 Efficient mass‐conservative numerical schemes for multiphase and multicomponent flow and transport modelling environmental subsurface systems 1‐02‐48 Computational advances in evolving interfaces 1‐02‐49 Advances in discontinuous Galerkin methods 1‐02‐50 Efficient methods for Hamilton–Jacobi equations 1‐02‐51 Least‐squares finite‐element methods for partial differential equations 1‐02‐52 FETI, balancing, and related hybrid domain‐decompositionmethods 1‐02‐53 Challenges for the accurate solution of Laplace eigenvalue and scattering problems 1‐02‐54 Interface methods and applications in multi‐phase problems 1‐02‐55 Partial differential equations and Sobolev gradients 1‐02‐56 High‐order compact schemes for partial differential equations 1‐02‐57 Multigrid methods for systems of PDEs 1‐02‐58 Recent advances in numerical multiscale methods 1‐02‐59 Recent advances in algebraic multigrid with applications 1‐02‐60 Adaptive and multilevel methods: design, analysis, and application 1‐02‐61 Adaptive and multilevel methods in electromagnetics 1‐02‐62 A posteriori error estimates and multi‐grid methods for eigenvalue problems 1‐02‐63 From differential geometry to compatible discretization 1‐02‐64 Current advances in domain decomposition methods and an outlook into the future 1‐02‐65 Numerical methods for data‐assimilation problems 1‐02‐66 Complexity of high‐dimensional problems ICIAM07 Minisymposia: 03 Nonlinear Analysis and Dynamical Systems 1‐03‐01 Computational topology and dynamics 1‐03‐02 On fractional calculus and its applications 1‐03‐03 Bifurcation analysis in experiments 1‐03‐04 Dynamical systems with cosymmetry: numerics, bifurcations, applications 1‐03‐05 Pattern formation in coupled‐cell systems 1‐03‐06 Geometry, dynamics, and control 1‐03‐07 Symmetry aspects in biological dynamical systems 1‐03‐08 Mathematical models and computational methods for nano‐ and bio‐technologies 1‐03‐09 Euler and space exploration ICIAM07 Minisymposia: 04 Partial Differential Equations linear and non‐linear 1‐04‐01 Anisotropic curvature flow and its applications 1‐04‐02 Viscosity solutions of partial differential equations: recent advances and applications 1‐04‐03 Applied mathematics in Latin America: part 1 1‐04‐04 Recent advances in the analysis of nonlinear parabolic equations and their singular limits 1‐04‐05 Numerical verification methods for solutions of partial differential equations 1‐04‐06 Nonlinear parabolic equations and their applications 1‐04‐07 Dynamics of nonlinear waves in heterogeneous media 1‐04‐08 Singular differential equations in applied mathematics 1‐04‐09 Qualitative properties of nonlinear hyperbolic equations 1‐04‐10 Quantum kinetic theory for Bose–Einstein condensation 1‐04‐11 Navier–Stokes equations and related topics 1‐04‐12 Extended splitting methods for partial differential equations: theory and application 1‐04‐13 Dynamical models and game theory 1‐04‐14 Free‐boundary problems and their applications 1‐04‐15 Free‐boundary problems: moving interfaces and applications 1‐04‐16 Control problems for fluidodynamic models 1‐04‐17 Non‐local conservation laws 1‐04‐18 Conservation laws with discontinuous flux 1‐04‐19 Nonlinear PDE techniques in imaging 1‐04‐20 Homogenization, inverse problems, and shape optimization 1‐04‐21 Non‐standard and problem‐oriented regularization methods 1‐04‐22 Inverse and ill‐posed problems in industry 1‐04‐23 Image processing based on partial differential equations 1‐04‐24 Inverse problems in financial modelling 1‐04‐25 Wave propagation in complex and random media 1‐04‐26 Boundary‐value problems and integral equations 1‐04‐27 Strongly‐nonlinear phenomena in optical and/or periodic media 1‐04‐28 Strongly‐nonlinear phenomena: theory, integrability and applications to hydrodynamics, Bose–Einstein condensation and biology 1‐04‐29 Analysis and numerical issues in kinetic equations ICIAM07 Minisymposia: 05 Applied Analysis 1‐05‐01 Compressed sensing 1‐05‐02 Compressed sensing: algorithms and applications 1‐05‐03 Trends in tomography 1‐05‐04 Mathematical challenges in the geosciences 1‐05‐05 Bregman distances in optimization, inverse problems and financial mathematics 1‐05‐06 Microstructures, PDE and applications 1‐05‐07 Mathematical aspects of materials science 1‐05‐08 Mathematical aspects of materials science: plasticity and fracture 1‐05‐09 Wavelet methods for real‐world problems 1‐05‐10 Approximation and analysis on the sphere 1‐05‐11 Approximation and point distribution on the sphere ICIAM07 Minisymposia: 06 Optimization 1‐06‐01 Applied topological methods 1‐06‐02 Advances in interior point methods 1‐06‐03 Industrial organization and game theory 1‐06‐04 Applied mathematics in Latin America: part 2 1‐06‐05 PDE‐constrained optimization: numerical analysis and scientific computing 1‐06‐06 Multidisciplinary optimization in simulation‐based design 1‐06‐07 Modelling and design of complex systems 1‐06‐08 Multigrid/multilevel approaches to the optimization of systems governed by partial differential equations 1‐06‐09 Max‐flow–min‐cut for continuous flows and related problems 1‐06‐10 Optimal control, estimation, and design for systems governed by partial differential equations: theory and computational methods 1‐06‐11 Optimal control and stability analysis in dynamical systems, involving parameters 1‐06‐12 Optimal control of industrial applications modelled by ODEs and PDEs 1‐06‐13 Optimal control with PDEs on gas networks 1‐06‐14 Preconditioned iterative methods for PDE constrained optimization 1‐06‐15 Optimization for sys